Terrorism by media: Coverage of the Ahmed Zaoui affair - Steven Price (Asia Pacific Network, 2004)
Last year [2003], in a supremely hypocritical editorial, The New Zealand Herald laid into the New Zealand Security Intelligence Service (NZSIS) for its ‘farcical level of research’ on Ahmed Zaoui.1 Zaoui is an Algerian national who turned up at Auckland International Airport in early December 2002, and asked for political asylum. He was immediately imprisoned. Relying on classified NZSIS information, the Minister of Immigration has declared Zaoui a threat to national security and issued a Security Risk Certificate against him, allowing his continued detention. The Herald pointed to the just-released decision of the Refugee Status Appeals Authority 2, which had found no credible evidence that Zaoui was a terrorist.